Influence of mold design and injection parameters on warpage deformation of thin-walled plastic parts - Wang, Bo; Cai, Anjiang (Polimery, 2021)
Thin-walled plastic parts are susceptible to deformation during injection molding. Using the example of a notebook battery cover, optimization of the injection mold design and injection process parameters was performed with Moldflow software, which resulted in about 69% reduction of the deformations. Moreover, the uneven material shrinkage during the injection process has been shown to be the main cause of deformations of thin-walled plastic parts.